ANALISIS PENGARUH SEKTOR INFORMAL, PRODUK DOMESTIK REGIONAL BRUTO, INDEKS PEMBANGUNAN MANUSIA, DAN UPAH TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI JAWA TIMUR TAHUN 2018-2021 - Dika Pramana Aditiya; Wildana, Muhammad Dandy Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
East Java is one of the densely-populated provinces in Indonesia. its population is dominated by working age, and indirectly will affect the amount of workforce, and this will cause problems in employment. This research aims to see the effect of informal sectors, regional gross domestic product, human development index, and wages towards workforce participation in East Java Province. Analysis employed in this research is panel data regression. Results show that every variable shows different results towards workforce participation. Informal sector and wages variables are significant, meanwhile regional gross domestic product and human development index variables are insignificant.